Study on air-pipe cooling effect and cooling strategy of mass reinforced concrete wall - Fei Yan; Zhenyi Luo; Yan Geng; Xiongyan Li (Scientific Reports)
Abstract The artificial cooling of mass concrete during reconstruction is essential for preventing structural cracking due to hydration heat. For tanks and other mass post-tensioned prestressed concrete structures, pre-cooled air can be injected into prestressed rebar pipes to facilitate concrete cooling. This air-pipe cooling method eliminates the need for special cooling pipes embedded within the concrete. Thermos-fluid–solid coupling finite element (FE) models were used to assess the temperature distribution and cracking risk in mass concrete walls. The heat transfer coefficient at the concrete-pipe-air interface and its influence factors were researched in this paper. Multiple cooling strategies have been proposed, and comparative analyses have been conducted to identify the most effective cooling approach.